Treating Type 2 Diabetes With Early, Intensive, Multimodal Pharmacotherapy: Real-World Evidence From an International Collaborative Database - Matthew Anson; Ayesha Malik; Sizheng S. Zhao; Philip Austin; Gema H. Ibarburu; Shabbar Jaffar; Anupam Garrib; Daniel J. Cuthbertson; Uazman Alam (Journal of Diabetes Research)
Conclusions: In this real-world study, early, intensive polytherapy, targeting the distinct pathophysiological defects in T2D, is associated with significantly more favourable cardiorenal outcomes, compared to insulin and SU therapy.